2013
DOI: 10.1016/j.surfcoat.2012.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Cr2C3–NiCr VPS thermal spray coatings as candidate for chromium replacement

Abstract: The present investigation has been carried out with the aim of determining the tribological behavior of a VPS chromium carbide coating both in the as-deposited and heat-treated conditions. A commercial powder of Cr 2 C 3-25% NiCr was sprayed employing a VPS system (Medicoat AG, Switzerland) onto plain low carbon steel coupons. The samples were subsequently annealed for 2 h at 600°C, 800°C and 900°C in Ar. The microstructural characterization was carried out by using SEM and XRD before and after the heat treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…When the material consolidates, it forms coarser morphological structure. Before further processing and for practical applications, the workpiece should be ground again, as it is generally done after the thermal spray deposition [18], to level off the asperities and gain a uniform and homogeneous morphology. Although being a limiting assumption, in this work, the following characterizations were performed on the as-treated coatings to avoid the influence of reprocessing on material properties.…”
Section: Resultsmentioning
confidence: 99%
“…When the material consolidates, it forms coarser morphological structure. Before further processing and for practical applications, the workpiece should be ground again, as it is generally done after the thermal spray deposition [18], to level off the asperities and gain a uniform and homogeneous morphology. Although being a limiting assumption, in this work, the following characterizations were performed on the as-treated coatings to avoid the influence of reprocessing on material properties.…”
Section: Resultsmentioning
confidence: 99%
“…Coatings made of tungsten carbide are frequently applied to the restriction grit and slide gate orifices of catalytic towers in the chemical industry to offer wear and cavitation resistance [14]. Chromium carbide-based coatings: These coatings are frequently applied to different components, including boiler tubes and turbine blades, in the power generation sector to provide high-temperature erosion resistance [15]. The study aims to enhance the understanding of the microstructural and surface characteristics of the nano-composites coated with high velocity air-fuel technology, as well as their scratch resistance properties.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies [22][23][24][25][26][27][28] focused on the effects of heat treatments on the microstructure and mechanical properties evolution of thermally sprayed Ni-based coatings. It was shown that coatings heat-treated at 700 and 900 • C have a dense structure and low porosity.…”
Section: Introductionmentioning
confidence: 99%